Characteristic time for the scavenging of fine particles due to coagulation with coarse particles. (4th July 2021) - Park, Sung Hoon; Kim, Minjoong J.; Kim, Jae-Jin; Choi, Jin-Young; Lee, Daegyun
Abstract: This article suggests an approximate analytical solution for the characteristic time for the mass removal of fine particles due to coagulation scavenging by coarse particles. The characteristic scavenging time is expressed as a function of the mass concentration of coarse particles as well as the mass median diameters (MMDs) and geometric standard deviations of fine and coarse particles. The log-normal method of moments was used to take into account the polydispersity effects. The particle number concentration of coarse particles was found to be the most important factor determining the coagulation-scavenging rate. Sensitivity analyses were conducted to quantify the effects of the particle size distribution parameters. The characteristic scavenging times for three specific cases, urban aerosols, Asian dust particles, and indoor aerosols, are discussed based on the derived solution.